The Justice and Development Party and political reforms in Turkey after 2002: an analytical study - Shakir Nayyef Shakir; Barzan Jalal Hamid (Tikrit Journal For Political Science, 2025)
After winning the general elections in 2002, the Justice and Development Party (AKP) took power in Turkey under the leadership of Recep Tayyip Erdogan. This party has a conservative Islamic orientation that differs from the rest of the Turkish political parties, as it combines Islamic law, liberal democracy, and a Soviet economy. Since assuming power, the Justice and Development Party has implemented a series of political, economic, and even social reforms. The economic reforms focused on enhancing the individual income of the Turkish citizen, thanks to market liberalization measures, enhancing interest in the private sector, and attracting foreign investments. Politically, the party focused on promoting democracy and human rights, with some reform measures such as amending the constitution, improving minority rights, and promoting freedom of expression. However, the government was subjected to criticism internally and externally due to the measures taken by the Turkish government to suppress individual freedoms and restrict freedom of expression. In the years following the military coup in 2016, political tensions increased in Turkey due to regional conflicts and internal challenges, which affected the country’s domestic and foreign policy. Despite these, the Justice and Development Party remained the main political force in Turkey, and faces continuing challenges in its quest. To achieve a balance between applying Islamic law, democracy and achieving economic development.